Case report: ADHD and prognosis in tyrosinemia type 1 - Barone, Helene; Elgen, Irene Bircow; Bliksrud, Yngve Thomas; Vangsøy Hansen, Eirik; Skavhellen, Rita Rigmor; Furevik, Magne Ivar; Haavik, Jan (Frontiers in Psychiatry, 2023)
Neurometabolic disorders such as tyrosinemia type 1 (TYRSN1) may interfere with brain metabolism and show symptoms of attention-deficit hyperactivity disorder (ADHD) in patients treated with the enzyme inhibitor nitisinone [2-(2-nitro-4-trifluoromethylbenzoyl)-1,3-cyclohexanedione, NTBC]. It has been reported that ADHD treatment improves treatment compliance, which is imperative for the long-term prognosis of patients with TYRSN1. In this study, we report the case of a male patient who was diagnosed with TYRSN1 at 3 months of age and was subsequently treated with NTBC, restricted protein intake, and amino acids supplementation. At 7 years of age, he was referred for neuropsychiatric assessment, diagnosed with ADHD, and treated with methylphenidate. The effects of the treatment were monitored via parental interviews, questionnaires covering ADHD symptoms, and a continuous performance test. A reduction in ADHD symptoms, particularly inattentiveness, was observed across all measures. The early identification of ADHD and the treatment of neurometabolic disorders, such as TYRSN1, may be important from a lifetime perspective as this may improve the prognosis of the medical condition as well.